2021
DOI: 10.1093/jxb/erab272
|View full text |Cite
|
Sign up to set email alerts
|

Root stem cell niche networks: it’s complexed! Insights from Arabidopsis

Abstract: The presence of two meristematic cell populations in the root and shoot apex allow plants to grow indefinitely. Due to its simple and predictable tissue organisation, the Arabidopsis root apical meristem remains an ideal model to study mechanisms such as stem cell specification, asymmetric cell division and differentiation in plants. The root stem cell niche consists of a quiescent organizing center surrounded by mitotically active stem cells, that originate all root tissues. The transcription factors PLETHORA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…In summary, we found that in agreement with a previous report (Sarkar et al , 2007 ), high PLT expression in the QC‐region is promoted by WOX5, albeit in an indirect manner, possibly by other factors, such as the described WOX5‐induced TAA1‐mediated auxin biosynthesis (Savina et al , 2020 ; Pardal & Heidstra, 2021 ). This PLT expression confines WOX5 to a defined and restricted number of cells within the QC region.…”
Section: Discussionsupporting
confidence: 93%
“…In summary, we found that in agreement with a previous report (Sarkar et al , 2007 ), high PLT expression in the QC‐region is promoted by WOX5, albeit in an indirect manner, possibly by other factors, such as the described WOX5‐induced TAA1‐mediated auxin biosynthesis (Savina et al , 2020 ; Pardal & Heidstra, 2021 ). This PLT expression confines WOX5 to a defined and restricted number of cells within the QC region.…”
Section: Discussionsupporting
confidence: 93%
“…Side roots are morphologically undistinguishable from the PR. They are both maintained by the stem cell niche composed of a quiescent center (QC) and its surrounding stem cells that will form different tissue layers (Dolan et al ., 1993; van den Berg et al ., 1997; Bennett & Scheres, 2010; Torres‐Martinez et al ., 2019; Pardal & Heidstra, 2021). LRs originate from a subset of xylem pole associated pericycle cells, which are primed by temporal oscillations in auxin signaling that correlates with cell growth in the root meristem (Laskowski et al ., 1995; Dubrovsky et al ., 2000; Beeckman et al ., 2001; Dubrovsky et al ., 2008; Dubrovsky & Rost, 2012; Beeckman & De Smet, 2014; van den Berg et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…SHR , SCR , PLT1 , PLT2 , PLT3 , PLT4 , and BRAVO are key regulators of stem cell renewal and meristem activity (Pardal and Heidstra, 2021). Recently we have shown that SHR and SCR also have a pivotal role in promoting root growth through promoting cell elongation (Fu et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Many genes involved in stem cell homeostasis have been identified, such as the GRAS family members SHORT‐ROOT (SHR) and SCARECROW (SCR), the PLETHORA (PLT) family transcription factors, the WUSCHEL family member WOX5, and the auxin transporters PINs and AUXs (Pardal and Heidstra, 2021). Several groups of small peptides and their corresponding receptors have also been shown to be essential for root stem cell renewal, including the CLE family (Fletcher, 2020), the RGF family (Lu et al, 2020), and the RALF family (Blackburn et al, 2020).…”
Section: Introductionmentioning
confidence: 99%